Leveraging plastomes for comparative analysis and phylogenomic inference within Scutellarioideae (Lamiaceae) - Zhao, Fei; Li, Bo; Drew, Bryan T.; Chen, Ya-Ping; Wang, Qiang; Yu, Wen-Bin; Liu, En-De; Salmaki, Yasaman; Peng, Hua; Xiang, Chun-Lei (PLOS ONE, 2020)
Scutellaria, or skullcaps, are medicinally important herbs in China, India, Japan, and elsewhere. Though Scutellaria is the second largest and one of the more taxonomically challenging genera within Lamiaceae, few molecular systematic studies have been undertaken within the genus; in part due to a paucity of available informative markers. The lack of informative molecular markers for Scutellaria hinders our ability to accurately and robustly reconstruct phylogenetic relationships, which hampers our understanding of the diversity, phylogeny, and evolutionary history of this cosmopolitan genus. Comparative analyses of 15 plastomes, representing 14 species of subfamily Scutellarioideae, indicate that plastomes within Scutellarioideae contain about 151,000 nucleotides, and possess a typical quadripartite structure. In total, 590 simple sequence repeats, 489 longer repeats, and 16 hyper-variable regions were identified from the 15 plastomes. Phylogenetic relationships among the 14 species representing four of the five genera of Scutellarioideae were resolved with high support values, but the current infrageneric classification of Scutellaria was not supported in all analyses. Complete plastome sequences provide better resolution at an interspecific level than using few to several plastid markers in phylogenetic reconstruction. The data presented here will serve as a foundation to facilitate DNA barcoding, species identification, and systematic research within Scutellaria, which is an important medicinal plant resource worldwide.